A study on youth interest level towards agriculture industry / Heril Darwing and Mohd Rahmat Yudin - Darwing, Heril; Yudin, Mohd Rahmat (2012)
This study was conducted to survey on the youth's interest level towards agricultural industry. This study also examined the relationship between the perception and the interest of youth towards agricultural industry. The samples of 100 respondents in several universities and agriculture institute were selected to answer the questionnaire in this research. The result of this study identified that most of the youth were perceive and have a high level of interest towards agriculture industry.